MINIMASI BIAYA DISTRIBUSI MENGGUNAKAN ALGORITMA NEAREST NEIGHBOUR (STUDI KASUS STOCKIST PT. XYZ) - Abdul Ghofur; M. Fuad F. Mu’tamar (Agroindustrial Technology Journal, 2019)
Distribution is a process of delivering products from producers to consumers. The distribution process determines the selling price and improves the product, therefore determining the distribution route becomes important. at this time Stockist PT. XYZ determine the distribution route in the order of ordering from the store. The purpose of this study is to minimize distribution costs so as to increase profits. The nearest neighbor algorithm is one of the algorithms in Vehicle Routing Problem (VRP) that is used to determine the route in the distribution process based on proximity. The results of this study, the nearest neighbor algorithm can help the cost of PT. XYZ was 39.18% on March 5, 2019 and 0.82% on March 6, 2019.